BIODEGRADABLE SOLID WASTE MANAGEMENT AT UNIVERSITY TO ACHIEVE ECOEFFICIENCY - Bustamante Sánchez, Yolanda (2014)
Lima produces over 2 million tons of waste per year (2’123,016 tons of solid waste per year according to a report issued by the Ministry of Environment (MINAM). On average, every Peruvian produces 0.61 kg of solid waste per day. Urban organic solid waste, RSOU constitute about 70% of the total volume of waste generated, causing negative environmental impacts on population, environment and economy. The integrated management of RSOU and processes required from the UNIVERSITY ranging from source separation (organic, recycling and useless) to processing by composting as bio fertilizer and soil conditioner for improving green areas, air clean and improving quality of life and efficiency Eco educational service provided by the universities and the fulfillment of its role in education, research and outreach.